Two-Step Fabrication of Li4Ti5O12-Coated Carbon Nanofibers as a Flexible Film Electrode for High-Power Lithium-Ion Batteries - Zhang, Z.; Deng, X.; Sunarso, J.; Cai, R.; Chu, S.; Miao, J.; Zhou, W.; Shao, Zongping (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
A self-standing nonwoven flexible Li4Ti5O12/carbon nanofiber composite (denoted LTO/CNF) was synthesized by using a facile method involving the electrospinning fabrication of CNFs and chemical deposition of LTO over the CNF surface. Scanning electron microscopy and transmission electron microscopy analyses show that the LTO/CNF film is composed of 50±20nm diameter LTO polycrystalline particles distributed over 300±50nm diameter CNF nanofibers. The nitrogen sorption isotherm further reveals the existence of mesopores in the LTO/CNF film. The as-prepared LTO/CNF composite exhibits attractive rate capability for lithium-ion batteries (LIBs), delivering initial specific capacities of 158, 153, 146, 138, 131, 122, and 109mAhg-1 at rates of 1, 5, 10, 20, 30, 40, and 50C, respectively, and a very stable cycling performance during 500 charge and discharge cycles at 20C, which superior to electrodes made of commercial coarse-type LTO anodes. In addition, the electrochemical impedance is effectively reduced by fabricating the unique electrode architecture, which originates from the improved 3D conducting network and the nanocrystalline size of the LTO active phase. Electrospinning of CNFs and chemical deposition of a nanocrystalline LTO phase proves to be an effective and facile method to develop anodes for flexible LIBs with a wide range of potential applications.